LITERATURE REVIEW: Efek Dari Pemberian Proprioceptive Training Dan Strengthening Exercise Dalam Meningkatkan ROM Pada Pasien Sprain Ankle - M. Hasrat Seno Adji, (2020)
Introduction: Increase the Range of Motion in Sprain Ankle is influenced by the number of activities, especially in the average age of 18-40 years with the adult category.Objective: This study aims to examine the literature, journals, articles or research results with the topic of the Effects of Giving Proprioceptive Training and Strengthening Exercises in increasing the Range of Motion in Sprain Ankle Patients. Method: Search for sources of literature, journals, articles, research results in several databases such as Google Scholar, Elsevier, PEDro, PubMed by using certain keywords in the period 2015-2020. From the literature search results, it was found 5 articles met the source inclusion criteria. The methodological quality assessment of 5 articles was assessed using the Scimago Journal & Country Rank (SJR). Results: After a literature review of 5 articles showed that proprioceptive training and strengthening exercises were effective in increasing the range of motion in the ankle. Conclusion: Proprioceptive training and Strengthening exercise can significantly increase the range of motion in sprain ankle patients.